A comparative study of orphan drug prices in Europe. Issue 1 (1st January 2017) - Young, Katherine Eve; Soussi, Imen; Hemels, Michiel; Toumi, Mondher
ABSTRACT: Background and Objective : This study assessed price differences by comparing annual treatment costs of similarly available orphan drugs in France, Germany, Italy, Norway, Spain, Sweden, and UK. Methods : Annual treatment costs per drug were calculated using ex-factory prices from IHS POLI and country price databases. The treatment cost in the comparator country was compared to the UK and ratios were analysed. Subanalyses were done on disease areas and UK cost quartiles. Results : 120 orphan drugs were included. Compared to the UK, the average costs were more expensive in France (1.13), Germany (1.11), Italy (1.08), Spain (1.07), and were cheaper in Sweden (0.99) and Norway (0.88). The average ratios offered a restrictive view as ratios were greatly heterogeneous (0.26 to 1.92) which was also seen in the different disease areas. The averaged ratios varied minimally among the cost quartiles which shows that cost differences were similar for the most expensive and least expensive orphan drugs in the UK. Conclusions : Individual orphan drug prices can vary widely across European countries, although on average these differences are relatively minor. This study suggests that in Europe, we may not be able predict which country may have higher or lower prices for orphan drugs.